Clinical synopsis of COVID-19 : evolving and challenging - Prabhakar, Hemanshu; Kapoor, Indu.; Mahajan, Charu (Singapore : Springer, 2020)
Corona virus disease or COVID-19 or SARS-CoV-2 infection is the latest pandemic that has affected humans globally. The disease has manifested itself in several forms and is now the focus of research worldwide. This book covers all the clinical aspects of the novel corona virus disease, COVID-19, which is one of the most contagious diseases ever known. It includes topics related to basic sciences, such as the virology and pathophysiology of the SARS-CoV-2 disease. It includes chapters related to symptomatology of the disease and making diagnosis, preparation of the health care workers to deal with this global pandemic. The book includes chapters on anesthetic and intensive care management of COVID-19 disease victims as these topics are of vast importance. Additionally, it includes a chapter giving insight in to the ethical aspects of the issues raised regarding disposal of bodies of the victims, as this pandemic has taken many lives across the world. It includes a chapter on special considerations to patient population such as geriatrics, pediatrics and pregnant women. The book serves as a useful resource for practitioners and clinicians in any field of medicine. It is also relevant for residents, trainees, fellows pursuing their courses in emergency medicine, anesthesia and critical care as well as postgraduates and even undergraduates. The book will serve as a ready-reckoner and useful guide for physicians from varied specialties during their clinical practice.
Introduction -- History of Corona Virus Disease Pandemic -- Basic Virology and Pathophysiology of Corona Virus Disease -- Clinical Manifestations of Corona Virus Disease -- Diagnostic Approach to a Patient with Corona Virus Disease -- Therapeutic Approach to Corona Virus Disease -- Anesthetic Consideration for Patients with Corona Virus Disease -- Intensive Care Management of Corona Virus Disease -- Complications of Corona Virus Disease -- Psychosocial Issues Related to Corona Virus Disease -- Trauma Care and Corona Virus Disease -- Special Considerations -- Pregnant Patients -- Special Considerations -- Pediatric Patients -- Special Considerations -- Geriatric Patient -- Control of Spread of Corona Virus Disease -- Ethical Issues Related to Corona Virus Disease -- Webliography.
Includes bibliographical references.
Keywords: COVID-19.